2022
DOI: 10.3389/fenvs.2021.774164
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emissions and The Transport Sector in Malaysia

Abstract: Transport is an essential infrastructure for development. With its high share of gross domestic product (GDP), it makes a significant contribution to total CO2 emissions in Malaysia. It is therefore important to pay greater attention to reducing CO2 emissions and sustainable development in this sector. Therefore, this study aims at estimating the relationship between transport CO2 emissions and its key drivers using the Autoregressive Distributed Lag (ARDL) technique. The time period covered by the study exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…A new dynamic excited autoregressive distributed lag (ARDL) model was used to investigate the validity of the EKC hypothesis in the U.S. in the short and long term. Solaymani (2022) examined the Environmental Kuznets Curve (EKC) hypothesis for Malaysia's transport sector. It is shown that energy and environmental policymakers need to pay more attention to improving energy efficiency as Malaysia progresses towards the highest levels of income and welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new dynamic excited autoregressive distributed lag (ARDL) model was used to investigate the validity of the EKC hypothesis in the U.S. in the short and long term. Solaymani (2022) examined the Environmental Kuznets Curve (EKC) hypothesis for Malaysia's transport sector. It is shown that energy and environmental policymakers need to pay more attention to improving energy efficiency as Malaysia progresses towards the highest levels of income and welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, studies of [75], [76] argued that road transportation is responsible for a considerable part of global emissions. Thus, in order to reduce greenhouse gas emissions, reduce wastage, decrease financial losses and solve environmental pollution issues there is need for the provision of more efficient and dependable logistics infrastructure [26], [77][78][79][80]. Furthermore, overcoming the distribution challenges will require investments in temperature-controlled technology, implementation of robust information monitoring systems like the Geographical information system (GIS), Radio Frequency Identification Device (RFID), adaptation of SMART emission control technologies , frameworks and models and adherence to best practices in temperature management [33], [75], [81][82][83][84].…”
Section: Challenges Faced By Logistics Service Providers In Nigeriamentioning
confidence: 99%
“…Effective Temperature control Temperature monitoring and control, preservation of product shelf life [26], [80], [85] 3.…”
Section: Maintaining Product Shelf Life and Freshnessmentioning
confidence: 99%
“…Mikayilov et al (2018) and Solaymani (2020) found a positive relationship between CO 2 emissions and gross domestic product (GDP). At the sectoral level, an increase in transport value added stimulates CO 2 emissions from the transport sector (Solaymani, 2022). Evidence has also demonstrated that population is responsible for CO 2 emissions in the economy (Zhang G et al, 2018;Rahman et al, 2020).…”
Section: Vector Autoregression (Var) Modelmentioning
confidence: 99%